Presence of Exogenous Sulfate Is Mandatory for Tip Growth in the Brown Alga Ectocarpus subulatus - Siméon, Amandine; Kridi, Sonia; Kloareg, Bernard; Hervé, Cécile (Frontiers in Plant Science, 2020)
Brown algae (Phaeophyceae) are multicellular photoautrophic organisms and the largest biomass producers in coastal regions. A variety of observations indicate that their extracellular matrix (ECM) is involved with screening of salts, development, cell fate selection and defense responses. It is likely that these functionalities are related to its constitutive structures. The major components of the ECM of brown algae are b-glucans, alginates and fucose-containing sulfated polysaccharides. The genus Ectocarpus comprises a wide range of species that have adapted to different environments, including isolates of Ectocarpus subulatus, a species highly resistant to low salinity. Previous studies on a freshwater strain of E. subulatus indicated that the sulfate remodeling of fucans is related to the external salt concentration. Here we show that the sulfate content of the surrounding medium is a key parameter influencing both the patterning of the alga and the occurrence of the BAM4 sulfated fucan epitope in walls of apical cells. These results indicate that sulfate uptake and incorporation in the sulfated fucans from apical cells is an essential parameter to sustain tip growth, and we discuss its influence on the architectural plasticity of Ectocarpus.